REVITALIZING BALINESE MUSICAL IDENTITY THROUGH EXPERIMENTAL GONG KEBYAR: THE CREATIVE PROCESS OF THE FRAGMENTARY PERFORMANCE “JAPA TUAN” - I Wayan Gede Rikiana Adi Putra; I Gede Mawan; I Made Kartawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Balinese karawitan, particularly Gong Kebyar, ideally preserves traditional identity, philosophical depth, spiritual values, and local distinctiveness while remaining open to creative reinterpretation and experimental exploration in contemporary performing arts. However, studies on Gong Kebyar have often focused on history, technique, structure, or accompaniment function, while its role in reactivating Atma Kerthi, Geguritan Japa Tuan, Gamelan Penting Karangasem, and fragmentary performance without dalang as an integrated experimental-cultural process remains insufficiently examined. This study addresses how Balinese musical identity is revitalized through the experimental use of Gong Kebyar in “Japa Tuan” and what artistic-cultural contributions the work offers to local musical heritage and experimental performance. Using a qualitative, practice-based artistic research method with an R&D orientation, the study applies the Metamorphosis Completa model. Ulat for idea searching, observation, interviews, literature study, and cultural inspiration; kepompong for incubation, interpretation, musical experimentation, timbral exploration, and dramatic structuring; and kupu-kupu for composition, rehearsal, evaluation, revision, and final performance. The findings show that “Japa Tuan” revitalizes Balinese musical identity by transforming Atma Kerthi, Geguritan Japa Tuan, and Balinese musical traditions into new musical-performative expression. By expanding Gong Kebyar into a dramaturgical force and integrating Gamelan Penting Karangasem, bedug, gong beri, peluit, suling basur, vocality, movement, and visual elements, the work bridges preservation and innovation while opening new possibilities for contemporary karawitan.